2007
DOI: 10.1161/01.str.0000257312.12989.af
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Outcomes Among Patients With Stroke Associated With Insurance Status

Abstract: Background and Purpose-Despite well-documented discrepancies in many clinical conditions across insurance groups, limited research has examined insurance-related disparities for patients with stroke. This study examined the relationship between insurance status and hospital care for patients with stroke. Methods-Discharges with intracerebral hemorrhage and acute ischemic stroke were abstracted from the 2002 National Inpatient Sample. Neurologic impairment status and mortality were examined. Results-Compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 20 publications
1
67
0
Order By: Relevance
“…11,12,14 For example, LaPar et al 13 demonstrated that Medicaid insurance status was associated with the longest length of stay and highest total costs, whereas Medicaid and uninsured insurance status independently conferred the highest adjusted risks of mortality in patients undergoing major surgical operations. Similarly, Shen et al 15 reported that uninsured patients had a higher level of neurologic impairment, a longer average length of hospital stay, and higher mortality risk after an acute ischemic stroke. Limitations of the current study include the selection bias related to the database: only 20% of the US population is represented in the National Inpatient Sample.…”
Section: Resultsmentioning
confidence: 93%
“…11,12,14 For example, LaPar et al 13 demonstrated that Medicaid insurance status was associated with the longest length of stay and highest total costs, whereas Medicaid and uninsured insurance status independently conferred the highest adjusted risks of mortality in patients undergoing major surgical operations. Similarly, Shen et al 15 reported that uninsured patients had a higher level of neurologic impairment, a longer average length of hospital stay, and higher mortality risk after an acute ischemic stroke. Limitations of the current study include the selection bias related to the database: only 20% of the US population is represented in the National Inpatient Sample.…”
Section: Resultsmentioning
confidence: 93%
“…6,14,[17][18][19] The NIS was used in the current study because it is the largest all-payer national database. Thus, the NIS provides a broader perspective than regional or statewide databases, and, in contrast to single-payer databases, allows the impact of many different payer types, including self-pay and no charge, to be examined.…”
Section: Advantages and Limitations To The Study Designmentioning
confidence: 99%
“…3,[6][7][8]10,13,[16][17][18]20 In a recent retrospective chart review of the New Jersey Acute Stroke Registry of patients presenting with acute ischemic stroke, uninsured patients had higher mortality and longer lengths of stay than insured patients. a higher level of neurological impairment, higher mortality, and longer lengths of stay for uninsured patients.…”
Section: Discussionmentioning
confidence: 99%